DETERMINATION OF BASIC COMPETENCE IN THE PROFESSIONAL PEDAGOGICAL COMMUNICATIVE COMPETENCE OF FUTURE TEACHER - Kohut, Irina V. (Educological discourse, 2014)
The questions of the contents of professional-pedagogical communicative competence of future teacher are examined. The components of the contents and the components of the structure of professional-pedagogical communicative competence of future teacher are suggested.